Making Nitrogen Fertilizer using Cassava Leaves and Papaya Leaves on Chili Plants - Ella Oktaviana Siahaan; Kristin Wulan Liberti Vivanis Gulo; Ribka Darningsih; Sarah Sihotang (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Nitrogen is one of the macro nutrients to increase plant growth and production. Yogurt is a processed product which is a fermented milk product that has long been known and has a specific sour taste. Yogurt contains streptococcus thermophilus and lactobacillus bulgaricus bacteria that live in symbiosis. Sweet potato leaves Its nutritional value can be increased through fermentation because fermentation can increase protein digestibility, reduce crude fiber content, improve the taste and aroma of feed ingredients and reduce heavy metal levels. Sweet potato leaves contain crude fiber of 25.71%, 69.50% moisture content. Nitrogen 13.41% .. This research was conducted for 3 weeks. 2 weeks in the fermentation process of nitrogen fertilizer solution and 1 week of giving it to plants. The results showed that the stem height, leaf color of the chilies changed after giving nitrogen fertilizer.